Problems in a modern family - Bulatović Anđelka V. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
This text analyses the crisis undergone by contemporary family. Rapid changes in all segments of modern society leave considerable consequences on the condition, development, role and position of family within society. Contemporary family responded to the challenges of time by transforming its structure, relationships and function. The family, created under the conditions of fast technological development, rise of standards of living, urbanization, democratization of relationships, withstood the effects of modern civilization, social alienation and social inequalities. The fact that contemporary family is much more open is the very reason for its increasing instability and vulnerability: the family is facing numerous difficulties and problems (poverty, childless marriages, single fathers and mothers) seeking to endure and fulfill its presupposed functions and expected role.